Perbandingan Perlindungan Disabilitas di Indonesia dan Malaysia: Tinjauan Maqasid Asy-Syariâ€™ah - Putri Kartikasari (Academica: Journal of Multidisciplinary Studies, 2018)
People with disabilities are often considered one-sided by the community. They are considered unproductive, and often can be reproached. In this case the role of the state is needed to maintain and strengthen persons with disabilities in their lives. In this study, the author will examine the comparison of disability treatment in Indonesia and Malaysia, the review of the Maqasid ash-Shariah. In this case the author uses a type of library research that studies books and other scientific works. The result is known that Indonesia and Malaysia have carried out the protection of the nafs (soul) in terms of the Maqasid Asy-Sharia, but for the implementation it is more inclined to Malaysia through the legal efforts of the policy â€œBasis and Pelan Actions of Persons with No Effortâ€ (policy and National Plan of Action of Persons with Disabilities). This policy was made to remove the barriers of persons with disabilities from all physical, social, economic and cultural barriers. Where the government supervises and gives special attention. Whereas in Indonesia legal remedies already exist, namely in Law Number 8 of 2016, especially articles 6, 20 and 26. However, the implementation of this law for persons with disabilities is still lacking.Keywords: Disability, maqasid ash-sharia, Indonesia, Malaysia